The internet as a source for language learning and teaching - Abdurazokov, Ulugbek (Журнал иностранных языков и лингвистики, 2021)
On the face of the twenty first century, it seems to me there is no other way of linguistic acquisition as a non-native speaker in both convenient and comprehensible avenue, but The Internet Based Education (IBE). As our life is being computerized day by day, the day of replacement of modern technologies with traditional way of educating is not far away. While being the sufficient method of teaching and learning it has also side effects for building successful teaching/learning environment. In this article, I tend to share my findings on the topic.